Respuestas
Respuesta dada por:
2
4y+3x=8
8x-9y=-77
4y=8-3x
y=(8-3x)/4
substituiendo en la seguna ecuacion obtenemos:
8x-9(8-3x)/4=-77
de donde 8x*4-72+27x=-77*4
32x+27x-72=-308
59x=-308+72
59x=-236
x=-236/59
x=-4
entonces y=(8-3x)/4
y=(8-3*(-4))/4
y=(8+12)/4
y=20/4
y=5
Prueba
4y+3x=8
4*5+3*(-4)=8
20-12=8
8=8
8x-9y=-77
8*(-4)-9*5=-77
-32-45=-77
-77=-77
8x-9y=-77
4y=8-3x
y=(8-3x)/4
substituiendo en la seguna ecuacion obtenemos:
8x-9(8-3x)/4=-77
de donde 8x*4-72+27x=-77*4
32x+27x-72=-308
59x=-308+72
59x=-236
x=-236/59
x=-4
entonces y=(8-3x)/4
y=(8-3*(-4))/4
y=(8+12)/4
y=20/4
y=5
Prueba
4y+3x=8
4*5+3*(-4)=8
20-12=8
8=8
8x-9y=-77
8*(-4)-9*5=-77
-32-45=-77
-77=-77
Respuesta dada por:
1
Respuestas:
x = -4
y = 5
x = -4
y = 5
Adjuntos:
![](https://es-static.z-dn.net/files/dcc/c14c629bbce17c1c263d0ae556f854b4.png)
Preguntas similares
hace 6 años
hace 6 años
hace 9 años
hace 9 años
hace 9 años
hace 9 años